(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Evaluating patients who have sustained blunt abdominal trauma remains one of the most challenging and resource-intensive aspects of acute trauma care.6,7 The objective of this dissertation is to analyse the pattern of fatal abdominal injuries secondary to blunt force impact. Aim: The aim of this research is to analyze the pattern of fatal abdominal injuries secondary to blunt force impact Materials and Method: Detailed observations for 38 autopsies with evidence of fatal abdominal trauma during the period October 2014 to July 2016 were carried out. Routine information like age, sex, occupation brief facts of the cases collected from the inquest report. Clinical history like time of admission, and deaths and other relevant data was collected from the hospital case sheets and death summaries. Results: Analysis involves 38 autopsies with evidence of fatal abdominal trauma during the period October 2014 to July 2016. The most common age group involved was between 21-30 years of age comprising 26% of total 38 cases followed by the age group of 11-20 years comprising 21% of total cases. The most common cause of blunt fatal abdominal trauma was vehicular accident seen in 84% of cases. In 38 cases, it was found that 24 cases (63%) were dead on arrival. Amongst 32 vehicular accidents, a total of 21 pedestrians (66%) were killed in 38 fatal blunt abdominal trauma cases. Liver was the organ mainly affected in fatal blunt abdominal trauma followed by pelvic trauma and kidney. Haemorrhage accounted for the largest number of cases (94.74%). Conclusion: The present study emphasizes the need for adopting measures to prevent morbidity and mortality resulting from blunt abdominal trauma.